CEFR as Language Policy: Opportunities and Challenges - Kristof Savski (The English Teacher, 2021)
The Common European Framework of Reference for Languages (CEFR) has become one of the most widely cited documents in language education across the globe, its influence now felt far beyond the confines of Europe, the context for which it was originally produced. In Malaysia, CEFR was given particular prominence in the Malaysia Education Blueprint 2013-2025 and English Language Education Reform in Malaysia: The Roadmap 2015-2025, both of which positioned the framework as the primary yardstick by which curricula were to be developed and against which achievements (or lack thereof) were to be evaluated. This paper examines CEFR from the perspective of language policy, focussing particularly on the implications this document has for local agency in the Malaysian context. The paper begins by examining the constructs of language and language education underlying CEFR, pointing in particular to how these reflect the socio-political context for which the framework was developed. The next section examines how policy texts in the Malaysian context, in particular the 2015 Roadmap, have interpreted CEFR, highlighting in particular the way that these texts (as other policies across the globe) have tended to treat the CEFR reference levels as a global standard, with little scope for local agency. The final section considers alternative, localized models for using CEFR as language policy in Malaysia, in particular how the framework may be used in support of an inclusive agenda in which diversity and multilingualism are embraced.
Keywords: language policy, CEFR, teacher agency, localization